Penggunaan Premises and Conclusions Gapped terhadap Makna “Memukul Dengan Rotan” Berdasarkan Amsal 23:14 - Sualang, Farel Yosua; Butin, Mariam Van; Sumarmi, Ni Putu (Integritas: Jurnal Teologi, 2023)
Collections of Book Proverbs provide many thematic teachings such as: wealth, poverty, and parental upbringing to children. Much emphasis is also placed on teaching parents to children in collections of Proverbs, especially Proverbs 23:14. Proverbs 23:14 is widely used as a basis for teaching parents to children, especially in the meaning of the phrase "beat with a rattan." If using a qualitative sub-hermeneutic study, especially wisdom literature, this article finds the use of premises and conclusions gapped on the meaning of the phrase "beat with a rattan" in Proverbs 23:14. This is proven by the existence of a rationale for thinking in stich A in verse 14a from the use of "beating with a rattan" which gives consequences or results from wise upbringing to a child in stich B in verse 14b.